Pengaruh Motivasi Intrinsik Dan Ekstrinsik Terhadap Kinerja Karyawan Dengan Kepuasan Kerja Sebagai Variabel Intervening Di Badan Pusat Statistik Provinsi Daerah Istimewa Yogyakarta - Dharmayati, Agustina Siwi (Universitas Muhammadiyah Yogyakarta, 2015)
The purpose of this study is to examine and analyze the effects of intrinsic motivation and extrinsic motivation on the performance of employees in the Statistics of D.I. Yogyakarta Province. This study is also use job satisfaction as an intervening variable to analyze the effect of intrinsic motivation and extrinsic motivation on the performance of employees.The object of this study is the office of the Statistics of D.I. Yogyakarta Province, and the subject were all employees of the Statistic of D.I. Yogyakarta Province, with a total population of 72 employees. Overall these employees occupy the Division of Administration, Division of Social Statistics, Division of Production Statistics, Division of Distribution Statistic, Division of NWA, and Division of IPDS. Data was collected using a questionnaire method is to provide a list of questions or the questionnaire directly to the respondents, totaling 72 people.The data were examined and analyzed using the Smart-PLS. The results showed that the variable of intrinsic motivation and extrinsic motivation has a significant positive effect on job satisfaction. Furthermore, intrinsic motivation variables showed a significant positive influence on employee performance, but variable extrinsic motivation doesn’t have significant influence on the performance of employees. Then the job satisfaction is not mediating influence between intrinsic motivation on employee performance. And job satisfaction is not mediating influence between extrinsic motivation on employee performance.